Effects of Environmental Factors on the Growth, Optical Density and Biomass of the Green Algae Chlorella Vulgaris in Outdoor Conditions - Lavajoo Fatemeh; Dehghani Mohsen (Journal of Applied Sciences and Environmental Management)
Effect of environmental factors on the growth of the Chlorella vulgaris was studied. C. vulgaris was  cultivated in sterilized natural seawater enriched with F/2-Si medium. Then grow in bucket, tub and photobioreactor (PBR) in outdoor condition. The daily routine work consisted of culture checkups of optical density, biomass gains, atmosphere lux, culture lux, atmosphere temperature and culture temperature  were recorded. The highest biomass yields were (3.0 μg/ml-1) in December and (2.01 μg/ml-1) in November in PBR. The highest deviation was in atmosphere lux in time 8:30 (± 117.7) and lowest  deviation was in atmosphere temperature in time 15:00 (± 1.0499). Optical density (OD) indicated that the best growth of C. vulgaris in outdoor condition was obtained in 650 lux and also it increased with increasing amount of lux. Tub report of C. vulgaris showed different growing behaviors at the various concentration of light and at the different temperatures. Algal production in outdoor PBR is relatively inexpensive, but is only suitable for a few, fast-growing specie. Finally, this fact is noteworthy that in outdoor conditions, temperature and light have important role in growth of C. vulgaris in present study.  ©JASEM